Investigating The Role of the Dynamic Conversation Program in Developing Senior High School Students’ Communicative Competence: Dynamic conversation - Sabrina Nugroho; Nita Kaniadewi (Universitas Islam Negeri Palopo, 2026)
This study investigates the role of the Dynamic Conversation (DC) Program, a locally designed, structured speaking routine, in developing the communicative competence of senior high school EFL learners in Indonesia. Unlike conventional CLT activities, DC integrates teacher mediation, peer interaction, and formative feedback within a single recurrent instructional sequence, thereby offering a distinctive and replicable framework for oral communication development. Employing a qualitative descriptive design, the study recruited ten Grade Ten students through purposive sampling at SMA Islam Teratai Putih Global, East Bekasi. Data were generated through semi-structured interviews, structured classroom observation, and document analysis. Five interrelated themes emerged: (1) enhanced speaking fluency and productive vocabulary through iterative practice; (2) contingent teacher scaffolding aligned with learners’ Zone of Proximal Development; (3) reduction of language anxiety and increased willingness to communicate; (4) integrated speaking–writing development reinforcing grammatical accuracy; and (5) motivational engagement sustained by progress-tracking artefacts. These findings suggest that DC may simultaneously address cognitive, affective, and motivational dimensions of communicative competence, offering a theoretically grounded and practically viable pedagogical innovation for EFL speaking instruction at the secondary level in Indonesia.